Histone H3 gene is not a suitable marker to distinguish Alternaria tenuissima from A. alternata affecting potato - Zhang, Yue; Tian, Peiyu; Duan, Guohua; Gao, Fangluan; Schnabel, Guido; Zhan, Jiasui; Chen, Fengping (PLOS ONE, 2020)
Potato Alternaria leaf blight is one of the economically most important disease in potato production worldwide. A recent study reported a quick method to distinguish main Alternaria pathogens A. tenuissima, A. alternata, and A. solani using partial histone H3 gene sequences. Using this method, our collection of 79 isolates from 8 provinces in China were presumably separated into A. tenussima and A. alternata. But in depth morphological and genetic analysis casted doubt on this identification. Culture morphologies of six presumed A. alternata isolates (PresA_alt) and six presumed A. tenuissima isolates (PresA_ten) were not significantly different. PresA_ten isolates also produced conidia in branched chains which supposed to be A. aternata. Phylogenetic analyses were conducted using internal transcribed spacer region (ITS) and five genes commonly used for species identification including glyceraldehyde-3-phosphate dehydrogenase (GPDH), translation elongation factor 1-alpha (TEF1), β-tubulin, plasma membrane ATPase (ATPase), and calmodulin genes. The results showed that GPDH and TEF1 sequences of PresA_alt and PresA_ten isolates were identical. The 12 isolates did not cluster by presumed species neither by individual or concatenated sequence comparisons. The phylogeny–trait association analysis confirmed that the two group isolates were undistinguishable by those molecular markers. Analysis of histone H3 gene sequences revealed variable intron sequences between PresA_ten and PresA_alt isolates, but the amino acid sequences were identical. Our results indicate that the previously published method to distinguish Alternaria species based on histone H3 gene sequence variation is inaccurate and that the prevalence of A. tenuissima isolates in China was likely overestimated.